Development of a new additive manufacturing platform for direct freeform 3D printing of intrinsically curved flexible membranes - Tan, Wen See (2022)
The wearable technology market has been expanding from wearable medical devices for non-invasive continuous monitoring of patient vital signs to wearable devices for tracking fitness activities that any person can access. Regardless of their form or function, desirable characteristics of wearable devices are the ability to be flexible, conformal, and easily attachable to the human body. However, as the human body is intrinsically curved and irregular, flat devices often have poor interfacial adhesion with the human body. This often leads to interfacial delamination and eventual detachment of the device. Therefore, a new additive manufacturing (AM) platform, a direct freeform 3D printing process (DF3DP), is proposed to allow direct construction of intrinsically curved 3D surfaces during the material deposition phase without the need for any pre-shaped supporting molds or templates. This 3D freeform printing process involves a supporting matrix made up of calcium alginate microgels, printing material made from silicone ink, and freeform printing paths derived from customized G-codes that conform exactly to the scanned human surface profile. Curved meshes mimicking the human elbow were used as a demonstration. A static contact stability test showed that the printed 3D silicone mesh was highly conformal to the model elbow surface as compared to a 2D flat mesh. A dynamic contact stability test was also conducted by subjecting both meshes to 100 cycles of mechanical flexion and extension, proving that intrinsically curved surfaces can provide better contact stability for complex human body surfaces undergoing motion than can flat surfaces. These results have proven that intrinsically curved membranes or structures fabricated by DF3DP can reduce the interfacial shear stress and occurrence of cracks and delamination while maintaining structural integrity and stability during use without compromising the comfort of the users. Our approach can resolve interfacial issues in flexible substrates and has great potential for epidermal devices or soft robotics via its long-term sustainable performance.